Study of seed protein electrophoretic profiles in some Erodium (Geraniaceae) species native to Iran - Keshavarzi, Maryam; Taghipour, Elham; Ghadam, Parinaz; Bokaee, Zahra Nazem (Acta Biologica Szegediensis, 2014)
Erodium (L.) L’Hér. with 75 species is the third largest genus in Geraniaceae. Erodium is distributed in all continents but it shows a great diversity in the Mediterranean region. In Flora Iranica , Schonbeck-Temesy (1970), 15 species, four subsections and three subspecies have been mentioned for Erodium in Iran. Electrophoretic patterns of seed storage proteins in the genus Erodium has not been studied extensively. In this study for the first time seed protein electrophoretic patterns of seven Erodium species from different regions of Iran have been investigated. Protein extracts of seeds were obtained and protein concentration was determined by the Bradford method and analyzed with SDS-polyacrylamide gel electrophoresis (SDS-PAGE). Results were evaluated by multivariate analysis methods including cluster analysis and factor analysis. In the electrophoretic pattern of seed storage proteins, generally, 48 specific bands with molecular weight between 13-102 kDa were detected. Electrophoretic data confirmed sub-generic classification of Erodium (to Plumosa and Erodium sections). Species relationships are discussed.